OBJECTIVES OF STUDENTS TO ENROLL IN SWIMMING CLASSES AT THE GYM IN THE METROPOLITAN AREA OF SANTOS. (Fiep Bulletin - online, 2013)
The swimming practice is currently largely sought for many reasons, however, it's traditionally believed that the students who look for programs related to this activity have, as main objective, the purpose of learning the four strokes culturally determined (front stroke, backstroke, breaststroke and butterfly stroke), however, a significant number of individuals who practice this activity want it for different reasons, among others, prophylaxis, physical dysfunction recovery, weight loss, and even improvement of their performance in other sports activities. This study main objective was to chart the real reason for the students to enroll in swimming courses in the coast area of São Paulo. The study was performed with 549 students, from 23 different gyms of the metropolitan area of Santos. To analyze the data, the individuals were sorted in 5 groups: elderly (over 60 years old), middle age (40 to 60 years old), adult (20 to 40 years old), teenager (10 to 20 years old) and general. The students had to answer to a survey with 10 items, which order was chosen randomly: 1st - Prevention of diseases (PD), 2nd – Physical dysfunction recovery (PDR), 3rd – Weight loss (WL), 4th – Muscles definition (MD), 5th – Overcome the fear of water (OFW), 6th – Learn the four strokes (LFS), 7th – Relieve stress (RS), 8th – Make new friends (MNF), 9th – Leisure and recreation (LR), 10th – Training for competitions (TFC). The survey was made so that each item was numbered from 1 to 10, being 1 for the most relevant and 10 for the least relevant. By sorting the interest of the students, it's clear that learning the 4 strokes wasn't the main reason for any of the different age groups that were analyzed, so, the structure of the swimming programs seems to need new objectives that raise the development of different strategies to different groups.
Keywords: Swimming; Purpose; Participants